Integrin regulation of cell signalling and motility. (1st June 2004) - Juliano, R.L.; Reddig, P.; Alahari, S.; Edin, M.; Howe, A.; Aplin, A.
Abstract : Integrins clearly play a key role in regulating both mitogenic signalling and cell migration. Thus integrins modulate the efficiency of the Erk (extracellular-signal-regulated kinase)/MAP kinase (mitogen-activated protein kinase) pathway, acting at several distinct levels. We have shown that both cAMP-dependent protein kinase and PAKs (p21-activated kinases) play a role in integrin regulation of the Erk pathway, acting primarily at the level of Raf-1. Integrins and PAKs also play a role in the control of cell migration. Thus we have discovered a novel protein that links the α5β1 integrin to migration controlled by Rho-family GTPases. This protein, termed Nischarin, is a large cytosolic macromolecule that is not related to well-known protein families. The N-terminus of Nischarin interacts with a short segment of the cytoplasmic domain of the α5 integrin subunit. Overexpression of Nischarin alters actin organization and inhibits Rac-driven cell migration and tumour cell invasion. Use of effector domain mutants of Rac suggest that Nischarin acts downstream of Rac, probably at the level of PAK-family kinases. These studies emphasize the intricate connection between integrins and Rho-family GTPases and their effectors in controlling both mitogenesis and migration.